2008
DOI: 10.5055/ajrt.2008.0012
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the “Stirrup Some Fun” therapeutic horseback riding program: A qualitative investigation

Abstract: Therapeutic horseback riding is an intervention utilizing horses in the treatment of individuals with emotional, cognitive, and/or physical disabilities. The purpose of this study was to investigate the perceived impact of a therapeutic riding program on children with mild to moderate physical and mental disabilities. Two groups of participants including five children (with a variety of physical and cognitive disabilities) and at least one parent of each of the five children were interviewed to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…One parent reported that following interaction with the horse his autistic child was able to better interact with other individuals. This finding confirms that of Elliott et al ( 2008 ) who asserted that communication with a horse might be easier for children with disabilities as the animal is non-judgmental. The bond that develops between the children and the horses allows them to develop qualities such as empathy, affection and confidence.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…One parent reported that following interaction with the horse his autistic child was able to better interact with other individuals. This finding confirms that of Elliott et al ( 2008 ) who asserted that communication with a horse might be easier for children with disabilities as the animal is non-judgmental. The bond that develops between the children and the horses allows them to develop qualities such as empathy, affection and confidence.…”
Section: Discussionsupporting
confidence: 91%
“…Postural control and balance (Bertoti 1988 ; Land, Errington & Paul 2002 ; Scialli 2002 ) as well as coordination (Brock 1990 ; Scialli 2002 ) is another set of physical functions that have been reported to improve following THR. Psychological functions, like a sense of accomplishment and achievement (All et al 1999 ; Davis et al 2009 ; Elliott, Funderburk & Holland 2008 ), resulting in increased self-confidence self-esteem, and self-worth, occurred following THR (All et al 1999 ; Bass et al 2009 ; Drnach et al 2010 ; Lessick et al 2004 ; Scialli 2002 ; Surujlal & Rufus 2011 ). Riding gives people with disabilities a chance to participate in and succeed at something that many people without a disability may hesitate to try (All et al 1999 ; Lessick et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in one later U.S. qualitative study, Miller and Alston [16] described, through perceptions of included parents, improvements in the social and academic development of children with disabilities. The positive effects of THR on self-confidence, self-esteem, and self-worth of children with mild to moderate physical and mental disabilities were noted by parents in a study by Elliot et al [17]. Similar experiences were also described in an Australian study in which parents of children with cerebral palsy reported that THR had a positive effect on their children's confidence and fear of heights [18].…”
Section: Introductionmentioning
confidence: 54%